Global Aromatic Ring Currents in Neutral Porphyrin Nanobelts - Vitek, Marco; Deng, Jie-Ren; Anderson, Harry L; Rončević, Igor (ACS nano, 2025)
The ability of a ring-shaped molecule to sustain a global aromatic or antiaromatic ring current when placed in a magnetic field indicates that its electronic wave function is coherently delocalized around its whole circumference. Large molecules that display this behavior are attractive components for molecular electronic devices, but this phenomenon is rare in neutral molecules with circuits of more than 40 π-electrons. Here, we use theoretical methods to investigate how the global ring currents evolve with increasing ring size in cyclic molecular nanobelts built from edge-fused porphyrins. Our results indicate that a global ring current persists in neutral nanobelts with Hückel circuits of 220 π-electrons (22 porphyrin units, circumference 18.6 nm). Our predictions are validated by using coupled clusters to construct a density functional approximation (denoted as OX-B3LYP) that accurately describes these nanobelts and by checking compliance with Koopmans' theorem.
Keywords: porphyrin nanobelts; ring current; aromaticity; molecular electronics; density functional theory